2014
DOI: 10.1016/j.juro.2013.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Hybrid Malignancy in a Solitary Sporadic Solid Benign Renal Mass: Implications for Treating Patients Following Renal Biopsy

Abstract: INTRODUCTION AND OBJECTIVES Concern regarding coexisting malignant pathology in benign renal tumors deters renal biopsy and questions its validity. We examined rates of coexisting malignant and high grade pathology in resected benign solid solitary renal tumors. METHODS Using our prospectively maintained database we identified patients with solitary solid renal tumors who underwent surgical resection between 1994 and 2012 (n=1829). Lesions containing elements of renal oncocytoma (RO), angiomyolipoma (AML) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…Also, certain diagnostic groups are difficult to diagnose in small specimens, especially classifying an oncocytic neoplasm as oncocytoma versus oncocytic/eosinophilic variants of chromophobe and clear cell RCC, respectively . Hybrid tumors have been described with mixed morphology of renal oncocytoma and chromophobe RCC, and chromophobe RCC, especially the oncocytic variant, may focally resemble renal oncocytoma . The 4 cases in our series diagnosed as oncocytoma did not have corresponding surgical specimens for confirmation, and were diagnosed on CB by morphology and immunohistochemistry with or without special stains.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Also, certain diagnostic groups are difficult to diagnose in small specimens, especially classifying an oncocytic neoplasm as oncocytoma versus oncocytic/eosinophilic variants of chromophobe and clear cell RCC, respectively . Hybrid tumors have been described with mixed morphology of renal oncocytoma and chromophobe RCC, and chromophobe RCC, especially the oncocytic variant, may focally resemble renal oncocytoma . The 4 cases in our series diagnosed as oncocytoma did not have corresponding surgical specimens for confirmation, and were diagnosed on CB by morphology and immunohistochemistry with or without special stains.…”
Section: Discussionmentioning
confidence: 84%
“…10,22 Hybrid tumors have been described with mixed morphology of renal oncocytoma and chromophobe RCC, and chromophobe RCC, especially the oncocytic variant, may focally resemble renal oncocytoma. [33][34][35] The 4 cases in our series diagnosed as oncocytoma did not have corresponding surgical specimens for confirmation, and were diagnosed on CB by morphology and immunohistochemistry with or without special stains. It has been recently suggested that oncocytic neoplasms are signed out as "renal oncocytic neoplasm" on small biopsies because RCC may uncommonly show focal areas resembling renal oncocytoma and due to the tumor heterogeneity of hybrid tumors.…”
Section: Accuracy Compared To Surgical Specimenmentioning
confidence: 99%
“…Classically, hybrid renal tumors have been seen as part of the renal syndrome of Birt-Hogg-Dube or in renal oncocytosis, but they can be seen sporadically [47]. In a retrospective study of 147 solitary solid renal masses classified as benign or oncocytic, 3 % showed a coexisting hybrid malignancy [48].…”
Section: Oncocytic Renal Tumorsmentioning
confidence: 99%
“…In addition, some hybridrenal lesions may contain distinct regions of both oncocytoma and RCC within it, thereby being prone to sampling error even if the obtained tissue is confidently interpreted by the pathologist. 108 Given these pitfalls, we suggest that, even when a renal mass biopsy returns a diagnosis of oncocytoma, continued imaging surveillance should be pursued to ensure continued stability.…”
Section: Clinical Role Of Mri In Localized Diseasementioning
confidence: 99%